تأثير توظيف التقنيات الحديثة في التعليم والصعوبات التي تواجهها من وجهة نظر المعلمين في محافظات (دمشق-اللاذقية-طرطوس) (Latakia University Journal - Economic and Legal Sciences Series, 2015)
هدفت هذه الدراسة إلى التعرف على التقنيات الحديثة المستخدمة حالياً في التعليم ومدى توظيف هذه التكنولوجيا والاستفادة منها في تطوير التعليم, وكذلك التعرف إلى أهم المعوقات التي تواجه استخدام هذه التكنولوجيا وصولاً إلى تقديم بعض المقترحات والتوصيات, ولأجل تحقيق هذا الهدف تم اختيار عينة عشوائية من المعلمين في المدارس بحجم (352) وأُجريت عليها التحليلات الإحصائية اللازمة لتتوصل الدراسة إلى النتائج التالية: 1-هناك توظيف للتقنيات الحديثة  في تطویر التعليم بمتوسط عام قدره2.818 2-عدم وجود فروق جوهرية في درجة توظيف التقنيات الحديثة في تطوير التعليم من وجهة نظر الأفراد أنفسهم تُعزى إلى الجنس والمؤهل العلمي. 3-وجود فروق جوهرية في درجة توظيف التقنيات الحديثة في تطوير التعليم من وجهة نظر الأفراد أنفسهم تُعزى إلى الخبرة الوظيفية The present study aims at clarifying the state of utilizing educational technology in general education in Syria. It also attempts to shed some light on the difficulties faced in using such technology. To achieve this, a random sample consisted  of (352) members was chosen from interviews with a number of school principals. The findings of the study were as follows: • There is an utilizing educational technology in development of education by  general mean its value 2.818,• There were no significant differences in utilizing educational technology in educational development  from the perspective of the teachers due to gender.• There were significant differences in utilizing educational technology in educational development from the perspective of the teachers  due to. Education.• There were significant differences in utilizing educational technology in educational development from the perspective of the teachers  due to the year of experience.